Is There a Digital World? Video Games as a Framework for Analyzing the Relations between Software and Lived Experience. - Possati, Luca M. (Techné: Research in Philosophy & Technology, 2021)
This article discusses the relation between software and human experience. I argue that software-based experiences are based on a radical discrepancy between the code and "lived experience." This break is different than the so-called "opacity" of technology. I start analyzing a case study: the video game Assassin's Creed: Odyssey. Video games are one of the most profound digital experiences humans can have. When I play a video game I do not see the code. However, the code is the source of my experience. I claim that the code's concealment is the necessary condition of the digital experience. I discuss the ontological definition of software as an entity. Software, I claim, is a complex object, composed of many different levels, whose unity is problematic. In the last part of the essay I argue that the break between lived experience and code is recomposed by imagination through the act of design.